Global burden of children and adolescents' nutritional deficiencies from 1990 to 2021 - Zhou, Juan; Li, Yangmei; Cai, Yixi (Frontiers in Pediatrics, 2025)
ObjectiveNutritional deficiencies critically impair growth and development in children and adolescents, yet comprehensive assessments of their global adolescent-specific burden are lacking. Adolescence represents a critical developmental window marked by rapid physical, cognitive, and psychosocial changes, making individuals particularly vulnerable to nutritional imbalances. This study aims to quantify the global burden of nutritional deficiencies in children and adolescents aged 0–19 years.MethodsUsing 2021 Global Burden of Disease (GBD) data, we assessed the global impact of nutritional deficiencies among children and adolescents by analyzing rates and absolute numbers. Joinpoint analysis and average annual percentage changes (AAPC) were applied to explore temporal trends from 1990 to 2021.ResultsIn 2021, nutritional deficiencies caused 85,886 deaths [95% uncertainty interval (UI): 78,203–93,452] and 25.6 million DALYs (UI: 23.3–27.9 million) among children and adolescents globally. Global mortality and DALY rates due to nutritional deficiencies in this population declined consistently from 1990 to 2021. Notably, the DALYs rates for protein-energy malnutrition, iodine deficiency, vitamin A deficiency, and dietary iron deficiency decreased globally, with the AAPC from 1990 to 2021 being −5.2 (−6.4 to −4), −2.8 (−3 to −2.6), −2.6 (−2.7 to −2.6), and −0.5 (−0.6 to −0.5), respectively. Despite these improvements, regions with lower Social Development Index (SDI), including low and low-middle SDI areas, the death rates and DALYs rates for nutritional deficiencies among children and adolescents remain high, although they have been declining over the 30-year study period. Africa and Asia continue to bear the greatest burden. At the age level, children under five exhibited the highest burden across all age groups.ConclusionsSince 1990, the global burden of nutritional deficiencies among children and adolescents have declined; however, it continues to be a significant public health issue, particularly in regions with low SDI. To mitigate this burden, more effective public health interventions are required.